Perlindungan Konsumen bagi Penumpang Pesawat atas Pembatalan Penerbangan - Imma Rahmani Hasanah; M. Amin El Walad Meuraksa (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Flight cancellation is a disruption in air transport services that causes losses to passengers, including time loss, additional costs and travel uncertainty. This article analyses the legal protection of air passengers affected by flight cancellations and proposes a more effective protection model. This study employs normative legal research using statutory, conceptual and limited comparative approaches to passenger-rights regimes in the European Union and selected international practices. The findings show that air passengers are both consumers of services and parties to a contract of carriage; therefore, they are entitled to information, safety, comfort, compensation, refund, rerouting and complaint mechanisms. In Indonesia, such protection is based on the Consumer Protection Law, the Aviation Law and technical regulations issued by the Ministry of Transportation. Nevertheless, implementation is still constrained by insufficient transparency of passenger rights, delayed refunds, standard clauses limiting airline liability and weak supervision and dispute resolution. This article recommends strengthening cancellation-notice standards, digitalising compensation claims, clarifying rerouting duties and improving administrative sanctions against airlines that fail to fulfil passenger rights.